THE EFFECT OF TOTAL ASSETS AND THIRD PARTY FUNDS ON FINANCING AT ISLAMIC BANK KB BANK 2020 TO 2023 - Ami Nullah Marlis Tanjung; M. Guffar Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2024)
The rapid growth of Islamic banking today, accompanied by an increase in the number of Islamic banking customers, is an interesting phenomenon in the midst of a dual banking system. This study aims to determine and analyse the effect of Total Assets and Third Party Funds on Financing at KB Islamic Banks from 2020 in the first quarter to 2023 in the fourth quarter. The data used is the financial report of KB Bank Syariah which has been published on the website www.kbbanksyariah.co.id. The method of analysis in this study is an associative method, with classical testing, and statistical analysis, namely multiple linear regression analysis. The variables of this study are Total Assets as variable X 1 and Third Party Funds as variable X 2 and Financing as Y. The results of the analysis using the statistical t test with a significant (α) = 0.05 using the sig value from the SPSS output obtained the significance value of each independent variable Total Assets (0.00) and Third Party Funds (0.655). The Total Asset variable alone has a partial influence on financing, while the Third Party Fund variable is far above the significance of 0.05 and this identifies that there is no partial influence on financing. The results of the analysis with the F test with a significance (α) = 0.05 obtained a significance of 0.000. This value is not greater than the significance value of 0.05 and this indicates that there is a significant relationship between Total Assets and Third Party Funds on financing simultaneously